Big Data Analytics 4th International Conference, BDA 2015, Hyderabad, India, December 15-18, 2015, Proceedings - Kumar, Naveen; Bhatnagar, Vasudha (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2015)
This book constitutes the refereed conference proceedings of the Fourth International Conference on Big Data Analytics, BDA 2015, held in Hyderabad, India, in December 2015. The 9 revised full papers and 9 invited papers were carefully reviewed and selected from 61 submissions and cover topics on big data: security and privacy; big data in commerce; big data: models and algorithms; and big data in medicine.